Liver Histophatological Studies of Mice (Mus musculus sp.) Infected With Gamma Rays Irradiated Plasmodium berghei Strains Anka - TUR RAHARDJO; SITI NURHAYATI; DWI RAMADHANI (Bogor Agricultural University, Indonesia, 2013)
Malaria is a serious global disease and a leading cause of morbidity and mortality in tropical and sub-tropical countries. Radiation attenuated vaccines have been demonstrated to be an effective means of controlling certain parasitic infections such as malaria. Our previous research showed that irradiation dose of 150-175 Gy to Plasmodium berghei were enable to suppress the infected erythrocyte cells and irradiation dose at 150 Gy was more effective compared to 175 Gy in attenuate the parasites based on parasitemia index. Aim of this research was to investigate the most suitable irradiation dose to attenuated P. berghei based on the the histological changes in the liver mouse malaria model. Histological changes in mice liver because of Plasmodium is congestion in the sinusoids and masses of hemozoin. Fourty Swiss mice were randomly assigned to four equal groups. First group of mice were inoculated with the unirradiated malaria parasites as a positive control while negative control group represented uninfected normal control. The third group of mice was inoculated with the irradiated malaria parasites with dose 175 Gy. Last group were inoculated with the irradiated malaria parasites with dose 150 Gy. Mice were sacrificed at day 6, 8, 12, 16, 20, and 24 post inoculation for liver histological study. Their livers processed for histomorphometric assessment of sinusoidal area, haemozoin area and hepatosomatic index as a quantitative measure of altered morphology. Hepatic sinusoidal area in mice infected with the unirradiated malaria parasites increased by 104% in day 24 post inoculated compared to day 6 post inoculated, whereas a smaller increase of 46% occurred in mice that were inoculated with the irradiated malaria parasites with dose 150 Gy. The difference between positive control and 150 Gy group was significant (P < 0.05). The highest average haemozoin area in all days post inoculation was in positive control whereas a smaller occurred in mice that were inoculated with the irradiated malaria parasites with dose 175 Gy, but the different was not significant (P > 0.05). For hepatosomatic index (HSI) at day 24 post inoculation the HSI value in group 150 Gy (5.33) was the smallest compared to other groups. Based on our research it can be concluded that irradiation dose at 150 Gy was more effective compared to 175 Gy in attenuate the parasites based on assessment of sinusoidal area, and HSI value at 24 day post inoculation.